Foragers of Africanized honeybee are more sensitive to fungicide pyraclostrobin than newly emerged bees - Eduardo da Costa Domingues, Caio [UNESP]; Bello Inoue, Lais Vieira [UNESP]; Mathias da Silva-Zacarin, Elaine Cristina; Malaspina, Osmar [UNESP] (My University, 2020)
The honeybee has economic importance both for the commercial value of bee products and for its role in the pollination of agricultural crops. Despite the fact that the fungicides are widely used in agriculture, studies comparing the effects of this group of pesticides on bees are still scarce. There are many gaps preventing the understanding of bees’ responses to exposure to fungicides, including the influence of the age of the exposed workers. However, this study aimed to compare the effects of residual concentrations of pyraclostrobin on young and old bees of Africanized Apis mellifera. The parameters analyzed were the survival rates, as well as the histopathological and histochemical changes in midgut of orally exposed workers to different sublethal concentrations of this strobilurin fungicide: 0.125 ng a.i./μL (C1), 0.025 ng a.i./μL (C2) e 0.005 ng a.i./μL (C3). The results showed a significant decrease in the longevity only for old bees exposed to the three concentrations of pyraclostrobin. After the five-day exposure period, the fungicide induced sublethal effects in the midgut only from the old bees. These effects were the increase both in cytoplasmic vacuolization of digestive cells and morphological changes in the nests of regenerative cells, which reflected in the higher lesion index of organ for groups C1 and C2. Additionally, there was a reduction in total protein staining in the intestinal epithelium in C1 and C2. At the same exposure period, the midgut of young bees presented only a reduction in the staining of neutral polysaccharides in the group C1. Concluding, old workers are more sensitive to the fungicide than young workers. This study showed different responses according to worker age, which can affect the maintenance of colony health. Future studies should take into account the age of the workers to better understand the effects of fungicides on bees.
Keywords: Apis mellifera; Longevity; Midgut; Morphophysiology; Strobilurin fungicide